Adiponectin Is a Candidate Biomarker of Lower Extremity Bone Density in Men With Chronic Spinal Cord Injury. (January 2014) - Doherty, Ashley L; Battaglino, Ricardo A; Donovan, Jayne; Gagnon, David; Lazzari, Antonio A; Garshick, Eric; Zafonte, Ross; Morse, Leslie R
ABSTRACT Adipose tissue is a major regulator of bone metabolism and in the general population obesity is associated with greater bone mineral density (BMD). However, bone‐fat interactions are multifactorial, and may involve pathways that influence both bone formation and resorption with competing effects on the skeleton. One such pathway involves adipocyte production of adipokines that regulate bone metabolism. In this study we determined the association between BMD, walking status, and circulating adipokines (adiponectin and leptin) in 149 men with chronic spinal cord injury (SCI). Although adipokine levels did not vary significantly based on walking status, there was a significant inverse association between adiponectin and BMD in wheelchair users independent of body composition. We found no association between adiponectin and BMD in the walkers and no association between leptin and BMD in either group. These findings suggest that for subjects with chronic SCI, walking may mitigate the effect of adiponectin mediated bone loss. For wheelchair users, adipose‐derived adiponectin may contribute to SCI‐induced osteoporosis because the osteoprotective benefits of obesity appear to require mechanical loading during ambulation. © 2014 American Society for Bone and Mineral Research.